The effect of demöoperidone on gallbladder and sphincter of oddi motility in human - Ender ELLİDOKUZ,; Ethem TANKURT,; Berna DEĞİRMENCİ,; Enis İĞCİ,; Hatice DURAK,; Ömür GÖNEN, (Turkish Journal of Gastroenterology, 2019)
-